Innovative personality traits and their relationship to the skills of standing on the hands and card will on the floor of the floor movements in your women's artistic gym. - Jabbar Mahmood, Sanarya (International Journal of Psychosocial Rehabilitation, 2020)
There are many attempts to study personality traits through different theories in the field of psychology, such as the theory of general patterns that tries to draw a descriptive picture of some general patterns under a broad framework of individuals, followed by the theory of features that form the individual through his characteristics and which can be distinguished from others. Innovation and qualities related to democracy are one of the most important factors of student and teacher success. The importance of the research lies in the importance of the aspects addressed in the study, as the phenomenon of innovation is a subject of concern for many researchers in the field of psychology and sports, through which students were directed and helped to develop their innovative aspects, which seems important and necessary for the individual and society alike. And the sport of gymnastics is one of the individual games that needs high possibilities in terms of skill and psychological to get achievement; the positive psychological experience enables the student to perform his difficult skill duties and increases his ability to bear all psychological burdens and personality features one of these psychological aspects that help to excel in the performance of kart will skills and stand on the hands on the carpet of the ground movements in the artistic skull, The search problem was solved in answering the following question:Do innovative personality traits have to do with the performance of the Kart Will skills and standing on the hands on the floor of the floor movements in your women's art gym?The second section included the methodology of research and its field procedures, in which the researcher used the descriptive approach to suit the nature of the problem of the research used.